The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/10826084.2020.1793365
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Drugs in the Nightlife Setting: Changes in Employee Perceptions and Drug Use over a Fifteen-Year Period

Abstract: Background: Illicit drug use is common in nightlife settings and associated with various public health-related problems, making this an important arena for prevention. Purpose/objectives: To assess perceived prevalence of illicit drug use in the Stockholm nightlife setting, use of and attitudes toward illicit drugs among employees at licensed premises. Also, to make comparisons with two identical measurements from 2001 and 2007/08, and to explore potential differences related to own drug use, type of licensed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 60 publications
(82 reference statements)
2
11
0
Order By: Relevance
“…Illicit drug use was common in all age groups but most prevalent among 22- to 28-year-olds. This is in line with previous research conducted in the nightlife setting among Swedish staff at licensed premises and among club goers in Norway, where past year drug use was higher among 18- to 25-year-olds than older age groups [ 20 , 56 ]. In addition, a Belgian study reported that last-year drug use was lower in nightlife goers above 26 years of age, which was suggested to be due to increased life responsibilities [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Illicit drug use was common in all age groups but most prevalent among 22- to 28-year-olds. This is in line with previous research conducted in the nightlife setting among Swedish staff at licensed premises and among club goers in Norway, where past year drug use was higher among 18- to 25-year-olds than older age groups [ 20 , 56 ]. In addition, a Belgian study reported that last-year drug use was lower in nightlife goers above 26 years of age, which was suggested to be due to increased life responsibilities [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…Compared with previous studies conducted in nightlife settings, the present study showed a similarly high prevalence of illicit drug use during the previous year as that among club goers in Norway (43%) [20] and among staff at licensed premises in Stockholm (47% among 18-to 24-year-olds) [56]. Furthermore, in line with previous studies, the most commonly used drugs were cannabis, followed by ecstasy, cocaine, and amphetamine [4,[11][12][13]15,17,20,[23][24][25][26][27]41].…”
Section: Prevalence Of Illicit Drug Use and Settings Where Drugs Are Usedsupporting
confidence: 87%
See 3 more Smart Citations